Towards a theory of presuppositions: Kuyperian contributions - Coletto, R. (Koers, 2011)
One of the most important themes of contemporary philosophy of science was the discovery of presuppositional beliefs and frameworks as factors influencing scientific research. This article explores the development of a theory of presuppositions within Kuyperian philosophy. The authors discussed in this study represent a few Kuyperian families: Dooyeweerd, Vollenhoven (briefly), Wolterstorff, Klapwijk, Duvenage and Botha. The perspective is both historical and systematic. Historically, it refers to the main authors who contributed to establishing the basic features of such a theory. Systematically, the article tries to evaluate the proposals of each contributor by assessing their value and limits. In doing so, the author often defends his own preferences and indicates the directions to be followed.